PEMBELAJARAN BAHASA INGGRIS BAGI SISWA MADRASAH IBTIDAIYAH BLORA - Diah soelistyowati; Sri Oemiati; Pipiet Furisari (STKIP Subang, 2022)
In the current era of globalization, learning a foreign language has become a necessity for everyone. Not only for adults, but for teenagers and children, the ability to speak foreign languages ​​really supports them to understand other knowledge, especially those using foreign languages. Learning in the scope of public schools under the auspices of the Ministry of National Education and schools under the auspices of the Ministry of Religion such as Madrasah Ibtidaiyah and the like have differences both in the types of lessons in the curriculum and the standards of each of these subjects. For schools that are under the auspices of the department of religion such as Madrasah Ibtidaiyah and the like, the foreign language included in the national curriculum is generally Arabic. While English is usually included in the realm of local content. For the practice of learning these English teachers must develop their own learning implementation plans that have not been included in the national curriculum. Likewise, learning English at Madrasah Khozinatul Ulum Blora, Central Java. Foreign language teachers at there, both English and Arabic try to use learning methods and strategies that can attract the attention of their students. This study aims to describe foreign language learning for students of Madrasah Ibtidaiyah in Blora. The target is expected to increase knowledge about foreign language learning for children and expand knowledge about foreign language learning for students of Madrasah Ibtidaiyah. Data collection techniques were carried out by observing learning activities and written documents. The research steps consist of 1) design 2) data collection 3) data processing 4) conclusion drawing, and 5) report writing. The data collection stage includes data categorization activities, and data analysis. The report writing stage includes report writing activities and research results presentation. The results of this study are expected to add insight and expand knowledge about foreign language learning for students of Madrasah Ibtidaiyah.